Living on the Edge: The Precariat Amid the Rental Crisis in the Metropolitan Area of Las Palmas de Gran Canaria (Spain) - Víctor Jiménez Barrado; José Ángel Hernández Luis; Antonio Ángel Ramón Ojeda; Claudio Moreno Medina (Urban Science)
This study examines access to rental housing in the metropolitan area of Las Palmas de Gran Canaria, linking it to socio-economic inequalities and the increasing precarization. In recent years, housing affordability has worsened due to rising rents, stagnant wages, and speculative dynamics—particularly those linked to tourism and platform-based economies. Drawing on official data from the State Reference System for Rental Housing Prices (SERPAVI) and income statistics at the census tract level, this research quantifies housing affordability and spatial disparities through indicators such as economic effort rates. The analysis identifies patterns of exclusion and urban fragmentation, showing that large sectors of the population—especially those earning the minimum age—face severe barriers to accessing adequate housing. The findings highlight the insufficiency of current public policies and propose the expansion of social rental housing and stricter rental market regulation as necessary steps to ensure fairer urban conditions.